Growth, yield, water use efficiency and competitive functions of intercropping system of maize (Zea mays L.) and mungbean (Vigna radiata L.) as influenced by irrigation - Roy, S; Barman, M; Puste, AM; Gunri, SK; Jana, K (SAARC Journal of Agriculture, 2016)
Field experiment was conducted at Instructional Farm, Jaguli (Mohanpur), Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India during two consecutive summer seasons of 2010-11, and 2011-12. The experiment was laid out in split-plot design having 4 levels of irrigation rainfed without mulch, rainfed with mulch, irrigation at IW (depth of irrigation water) / CPE (Cumulative pan evaporation) ratios of 0.5 and 0.75 in main-plot and 4 inter cropping systems, sole maize, sole mungbean, maize + mungbean (1:1 row ratio) and maize + mungbean (3:2 row ratio) considered as sub-plot treatments replicated thrice. Results revealed that application of irrigation and intercropping systems markedly influenced the growth, yield and yield components (number of cobs/plant, number of grains/cob in case of maize and number of pods/plant and number of seeds/pod in case of mungbean) where the maximum value of these components were recorded with the application of irrigation at IW/CPE ratio 0.75 in sole crop. Maize-mungbean in 3:2 row ratio yielded higher than that of 1:1 intercropping system which might be due to less light interception and more competition for water and nutrition between both the crops. CU of water increased with the increasing levels of irrigation and the maximum value (17.75 kg ha-1 mm- 1) of WUE (water use efficiency) was observed with irrigation at IW: CPE ratio 0.75 under intercropping system of maize : mungbean in 3:2 row ratio followed by IW: CPE ratio 0.50. Among the sole crop, maximum WUE was with IW/CPE ratio 0.75 might be due to more consumption of water corresponding to production potential of maize, while, it was more under rainfed with mulch in mungbean. The relative crowding coefficient (RCC) also revealed both the intercropping systems were advantageous and the land equivalent ratio (LER) increased with the level of irrigation.Thus, maize grown in association with mungbean (3:2 row ratio) were found to be more profitable (B:C ratio of 2.58) with higher monetary advantage as compared to sole crop of maize (B:C ratio of 1.98) with the application of irrigation at IW: CPE ratio of 0.75 in new alluvial zone of West Bengal. SAARC J. Agri., 13(2): 94-107 (2015)